Aplikasi teknik keringkam ke atas kepelbagaian material - Muhammad, Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2015)
~eringkam is the embroidery art or technique which is applied on gauze fabric to produce hawls or selayah to be worn in formal occasions or Sarawak Malay custom since many years ago. In addition, this Keringkam shawls is an art resulting from the intricate and fine handmade piece by the community ofMalay textile crafters who live by the shores. The embroidery is made using gold or silver coated soft steel tape. It is then embroidered on gauze using two techniques namely 'thread count' and 'piercing'. Therefore, these techniques are time consuming where limited end products were produced since its heyday until toda : The research objectives are to analyse the embroidery technique and to formulate simpler structure in forming the Sarawak Malay Keringkam embroidery motifs. The study involves experimentation of new and more structured formulation on variety of fabric materials. The new formula will decrease the duration of embroidering process and moreover, the technique will be easy to understand and learn. Also, this new technique is an innovation in producing keringkam which can be applied to the handicraft products extensively. Therefore, they have the potential to be commercialised and yet preserving the aesthetic value ofthe Sarawak Malay handicrafts.